PENINGKATAN KADAR HEMOGLOBIN DENGAN EKSTRAK BIT MERAH (Beta vulgaris L) PADA TIKUS Rattus norvegicus BUNTING ANEMIA - Dewita Dewita; Nova Sumaini Prihatin; Jasmiati Jasmiati (Jurnal Ilmiah Kebidanan Imelda, 2023)
Anemia is a major community health problem and is often found in communities and countries, especially in developing countries including Egypt and Saudi Arabia. norvegicus anemia. The study design was a pure experimental design with a pre-posttest control group design on 30 pregnant Rattus norvegicus white rats which were divided into 5 treatment groups randomly. There were 5 treatment groups, namely the negative control group, the positive control group was only induced into 5 treatment groups randomly. There were 5 treatment groups, namely the negative control group, the positive control was only induced, treatment I was induced by phenylhydrazine, treatment I was induced by phenylhydrazine with a dose of 0.04 mg/kg/BW + Red beet extract 150 mg/KgBW, treatment II was induced by phenylhydrazine. with a dose of 0.04 mg/kg/BW + red beet extract 300 mg/KgBW and treatment III was induced by phenylhydrazine at a dose of 0.04 mg/kg/BW + red beet extract was given 450 mg/KgBW. Samples were selected according to inclusion criteria, namely pregnant female white rats, female, 2-3 months old, body weight 120-200 grams, healthy and not anatomically deformed. Analysis of the data used is one-way ANOVA. there was a significant difference between data on hemoglobin levels of pregnant rats before and after treatment in the negative control group, treatment I and treatment II with p value <0.05. Giving red beet extract to pregnant rats with anemia can increase hemoglobin levels.